Developing a competency framework for practitioners of English for Specific engineering purposes (ESEP) - Nor Yazi, Khamis (2017)
The English for Specific Engineering Purposes (ESEP) competencies of ESL practitioners teaching English for Specific Academic Purposes (ESAP) at Malaysian engineering and technical (MTUN) universities is vital in ensuring quality learning and teaching of language and communication skills at those institutions. This study aims to develop a competency framework for ESEP practitioners at MTUN universities. The development of the framework was conducted in two phases using the exploratory sequential mixed methods. The first phase comprises qualitative data gathered from document analyses, related literature and semi structured interviews. This study is framed by the principles of Malaysian Teacher Standards (MTS) i.e. the Professional Values, Knowledge and Understanding, and Skills of Learning and Teaching. The principles are represented by Walker's Professional ELT Service Standards, Venkatraman and Prema's Competencies for Teachers of English in Engineering Colleges and BALEAP Framework. The second phase comprises quantitative data gathered from three Delphi rounds with 14 ESEP experts and a survey of 101 MTUN ESEP practitioners. Finding from the qualitative inquiry revealed evidence of the three principles in identifying the practitioners required competency which implicates two types of professional development training. Formal and informal. The quantitative analyses using SmartPLS software identified the second principle (ESEP Knowledge and Understanding) and 'patient when learners have difficulties in learning as the prevalent principle and competency item for ESEP practitioners. This confirms the importance of ESEP practitioners. This confirms the importance of ESEP practitioners, knowledge and understanding in engineering to elevate their status and recognitions, as well as enhance learners interest in learning the language. The competency framework for ESEP practitioners was also validated in terms of its realibility and validity based on a measurement model developed from the sofware. The framework could be a standard for the practitioners learning and teaching practices and employed as a standard evaluation for quality enhancement professional development training and recruitment purposes. The finding also implicate the need for the local quality agencies to specify a standard of competencies as a guideline for ESEP practitioners qualifications teaching at MTUN universities.